Accuracy and Reliability of Measurements Obtained from 3-Dimensional Rabbit Mandible Model: A Micro-Computed Tomography Study - Remzi Orkun Akgün (Sciendo, 2019)
The aim of this study was to evaluate the mandibular morphometric measurements of male and female rabbits using three-dimensional digital model and real bone measurements. Ten (5 female, 5 male) rabbits with no bone deformities were used in the study. Three-dimensional models were produced from two-dimensional microcomputed tomography images of the rabbit’s mandible. Biometric data were obtained by using the same measuring points over both three-dimensional models and real bone samples. There was only a significant main effect of gender for the greatest length of the mandible, length from aboral border of the alveolus of third molar teeth to infradentale, length of the diastema, height of the vertical ramus (measured in projection), distance from the incisor to the oral border of mental foramen, distance from aboral border of mental foramen to caudal border of mandible, distance between retroalveolar foramen and caudal border of mandible. For these measurements, calculated data for females are significantly higher than the males (p<0.05). It was found to be statistically significant between methods only for the length of the cheek tooth row and height of the vertical ramus values (p<0.05). In this study, it was understood that 3D morphometric measurements for bone tissue could be used with accuracy and reliability especially in anatomy and orthodontics areas as an alternative to traditional measurements made with a digital caliper.